Eldercare burden and employee’s performance: The roles of physical exhaustion and religiousness. - Fayyaz Ghafoor; Dr. Osaid Rabie (Review Journal of Social Psychology & Social Works, 2024)
This study examines the detrimental effects of employees' eldercare burden on job performance, mediated by physical exhaustion. This study discovered that employee personal resources of religiousness significantly moderate and mitigate the impact of eldercare burden on physical exhaustion. A longitudinal study employing a three-wave, multisource design, collected data from 373 employees across education, banking and healthcare sectors in Pakistan. The study's findings indicate a significant negative relationship between employee eldercare burden and job performance. Mediation analysis revealed that employee eldercare burden negatively impacts work outcomes via physical exhaustion. Employee religious beliefs mitigate the adverse effects of eldercare burden on physical exhaustion, demonstrating a weakened relationship among highly religious caregivers. The study identified a moderated mediation model, where religiousness influences the indirect relationship between eldercare burden and performance via physical exhaustion. The research expands on previous studies by examining the specific factors that contribute to the negative impact of eldercare burden on workplace performance, with findings indicating that physical exhaustion is primary mediator of this relationship. This dysfunctional effect of eldercare burden in turn, buffers due to religiousness, acting as shield against the spillover of workplace stress due to physical exhaustion and it promotes behaviors which ultimately promote employee’s performance. The findings of this study are intended to inspire organizational transformation, encouraging proactive strategies that address the eldercare burden, promote religious harmony, and enhance performance outcomes, ultimately contributing to the well-being of employees and the success of the organization.